What bycatch tells us about the diet of harbor and gray seals and overlap with commercial fishermen - Lyssikatos, Marjorie C.; Wenzel, Frederick W. (Frontiers in Conservation Science, 2024)
Northwest Atlantic harbor (Phoca vitulina vitulina) and gray (Halichoerus grypus atlantica) seal populations are recovering from early to mid-20th century exploitation, increasing their biological interactions and bycatch in Northeastern US commercial fisheries. We evaluated the seals’ diet composition and compared their prey to commercial catches to assess trophic overlap and potential competition with commercial fisherman target catches. We obtained 148 harbor and 178 gray seal stomach samples from bycatch events that occurred between 2004 and 2018. We learned from the hard part remains that the majority of seals bycaught are young-of-the-year (≤12 months old) that consume a wide breadth of prey across three trophic groups. There was a general dichotomy in extrinsic factors associated with seal diet in which 45% trophic niche separation was explained by non-overlapping harbor and gray seal phenology and pup haul-out locations that are adjacent to active fishing areas. Prey size estimated from fish otoliths and squid beaks recovered from stomach contents showed that gray seals consumed larger prey than harbor seals and prey sizes from both seals showed limited overlap with prey sizes caught by commercial gillnet fishermen. The most important prey to both seals included large (>20 cm) and small (≤20 cm) silver hake (Merluccius bilinearis), (≤40 cm) red hake (Urophycis chuss), gulf stream flounder (Citharichthys arctifrons), medium (21–40 cm) white hake (Urophycis tenuis), and (<50 cm) Atlantic cod (Gadus morhua). Important prey to harbor seals that did not overlap with gray seals were Acadian redfish (Sebastes fasciatus), Atlantic herring (Clupea harengus), longfin (Doryteuthis pealeii), and shortfin squid (Illex illecebrosus). They contrasted with prey important to gray seals that did not overlap with harbor seals: yellowtail flounder (Limanda ferruginea), sand lance (Ammodytes spp.), Urophycis spp., and fourspot flounder (Hippoglossina oblonga). Despite the potential bias associated with opportunistic bycatch sampling, this study demonstrates the importance and value of utilizing carcasses retained from bycatch events, is complimentary to newer methodologies (i.e., DNA meta-barcoding), and fills data gaps in our understanding of the role recovering harbor and gray seal populations have on Northeastern US regional food webs.